Monotonicity and bounds on Bessel functions - Larry Landau (Electronic Journal of Differential Equations, 2000)
survey my recent results on monotonicity with respect to order of general Bessel functions, which follow from a new identity and lead to best possible uniform bounds. Application may be made to the "spreading of the wave packet" for a free quantum particle on a lattice and to estimates for perturbative expansions.